2022
DOI: 10.1084/jem.20211291
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylserines derived from microbiota in Crohn’s disease elicit pathological Th1 response

Abstract: Microbiota alteration and IFN-γ–producing CD4+ T cell overactivation are implicated in Crohn’s disease (CD) pathogenesis. However, it remains unclear how dysbiosis enhances Th1 responses, leading to intestinal inflammation. Here, we identified key metabolites derived from dysbiotic microbiota that induce enhanced Th1 responses and exaggerate colitis in mouse models. Patients with CD showed elevated lysophosphatidylserine (LysoPS) concentration in their feces, accompanied by a higher relative abundance of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 69 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…On the other hand, in addition to supplementation of bacteria, in recent years there has also been a growing interest in targeting the bacterial products (such as using postbiotics) to alter the immune system to treat IBD. The findings of Otake-Kasamoto et al (2022) provide experimental evidence supporting LysoPS as a putative diagnostic biomarker and a future therapeutic target for CD. Nevertheless, considering the complex nature of LysoPS in regulating the responses of different immune cell types in a given tissue environment under a particular physiological or pathological condition, more research is needed to elucidate the precise role of LysoPS in CD before targeting these multifunctional bioactive lipids to treat human gastrointestinal disorders becomes a reality.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, in addition to supplementation of bacteria, in recent years there has also been a growing interest in targeting the bacterial products (such as using postbiotics) to alter the immune system to treat IBD. The findings of Otake-Kasamoto et al (2022) provide experimental evidence supporting LysoPS as a putative diagnostic biomarker and a future therapeutic target for CD. Nevertheless, considering the complex nature of LysoPS in regulating the responses of different immune cell types in a given tissue environment under a particular physiological or pathological condition, more research is needed to elucidate the precise role of LysoPS in CD before targeting these multifunctional bioactive lipids to treat human gastrointestinal disorders becomes a reality.…”
mentioning
confidence: 72%
“…By performing lipidomic analysis and shotgun metagenomic sequencing, Otake-Kasamoto et al (2022) observed that lysophosphatidylserine (LysoPS) was increased in feces of patients with CD, in addition to elevated relative abundance of microbes expressing phospholipid-hydrolyzing enzyme phospholipase A, the enzyme that generates lysoglycerophospholipids by hydrolyzing cell membrane phospholipid molecules. Moreover, when germ-free mice were inoculated with E. coli –enriched feces derived from patients with CD but not from the healthy donors, elevated concentration of LysoPS was also detected.…”
mentioning
confidence: 99%
“…The P2 receptor family has also been implicated in regulating the gut microbiota. 22 For instance, the P2X1 receptor has been shown to reduce inflammation in colitis, possibly via balancing gut microbiota. 23 However, it is still unclear whether the P2X4 receptor can influence colitis by modulating the gut microbiota balance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting gut microbiota has emerged as the most effective and ideal approach for preventing and treating IBD. The P2 receptor family has also been implicated in regulating the gut microbiota 22 . For instance, the P2X1 receptor has been shown to reduce inflammation in colitis, possibly via balancing gut microbiota 23 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that the lysoPS from L. plantarumderived extracellular vesicles might be indispensable for lipid-mediated intercellular communication within or between living organisms 52 . Recently, lysoPS derived from gut microbiota was found to elicit a T helper 1 (Th1) cell immunopathological response in Crohn's disease, including promoting IFN-γ-producing CD4 + T cell accumulation in the colon, enhancing Th1 cell effector functions, modulating Th1 cells bioenergetic metabolism and inducing Th1 cell epigenetic changes 135 . This suggests that bacterial lysoPS may be a relevant bioactive lipid factor in bacterial pathogenesis and intestinal inflammation progression.…”
Section: Lysophosphatidylserinementioning
confidence: 99%